Efficient protocol for backbone and side-chain assignments of large, intrinsically disordered proteins: transient secondary structure analysis of 49.2 kDa microtubule associated protein 2c - Nováček, Jiří; Janda, Lubomír; Dopitová, Radka; Žídek, Lukáš; Sklenář, Vladimír (Journal of biomolecular NMR, 2013)
Microtubule-associated proteins (MAPs) are abundantly present in axons and dendrites, and have been shown to play crucial role during the neuronal morphogenesis. The period of main dendritic outgrowth and synaptogenesis coincides with high expression levels of one of MAPs, the MAP2c, in rats. The MAP2c is a 49.2 kDa intrinsically disordered protein. To achieve an atomic resolution characterization of such a large protein, we have developed a protocol based on the acquisition of two five-dimensional (13)C-directly detected NMR experiments. Our previously published 5D CACONCACO experiment (Nováček et al. in J Biomol NMR 50(1):1-11, 2011) provides the sequential assignment of the backbone resonances, which is not interrupted by the presence of the proline residues in the amino acid sequence. A novel 5D HC(CC-TOCSY)CACON experiment facilitates the assignment of the aliphatic side chain resonances. To streamline the data analysis, we have developed a semi-automated procedure for signal assignments. The obtained data provides the first atomic resolution insight into the conformational state of MAP2c and constitutes a model for further functional studies of MAPs.
Keywords: proteiny asociované s mikrotubuly; Amino Acid Sequence; Animals; molekulární sekvence - údaje; glycin; Algorithms; Protein Structure, Secondary; Molecular Sequence Data; sekvence aminokyselin; algoritmy; nukleární magnetická rezonance biomolekulární; Nuclear Magnetic Resonance, Biomolecular; krysa rodu Rattus; Glycine; Rats; molekulová hmotnost; vnitřně neuspořádané proteiny; Molecular Weight; zvířata; Microtubule-Associated Proteins; sekundární struktura proteinů; Intrinsically Disordered Proteins